Uji Efektifitas Ekstrak Etanol 70% Herba Pegagan (Centella asiatica (L.) Urb.) Sebagai Peningkat Nafsu Makan Secara in vivo: Effectiveness Test of 70% Ethanol Extract of Gotu Kola Herb (Centella asiatica (L.) Urb.) as an Appetite Stimulant in vivo - Fajar Sandhori; Yusuf Alif Pratama; Hanif Rifqi Prasetyawan; Subhan Rullyansyah; Firmansyah Ardian Ramadhani (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2026)
Centella asiatica (L.) Urb. contain bioactive compounds such as triterpenoids, flavonoids, and phenolics with antioxidant activity that can increase appetite through an indirect orexigenic effect. This study aimed to evaluate the antioxidant activity and the effectiveness of the extract as an appetite enhancer in vivo. Extraction was performed using the Microwave-Assisted Extraction (MAE) method. Antioxidant activity was assessed using the DPPH method at a maximum wavelength of 517 nm. The in vivo study was conducted on male BALB/c mice divided into four groups (control, 100 mg/kg BW, 200 mg/kg BW, and 400 mg/kg BW). The results showed that the extract exhibited antioxidant activity with an IC₅₀ value of 50.16 ± 3.24 ppm, which was weaker than vitamin C (8.15 ± 0.72 ppm) . Appetite stimulation testing demonstrated increased feed intake at doses of 200 mg/kg BW (3.25 ± 0.36 g) and 400 mg/kg BW (3.88 ± 0.44 g) compared to the control (2.34 ± 0.43 g) and each group showed significant differences (p<0.05). These findings indicate that the 70% ethanol extract of Centella asiatica possesses moderate antioxidant activity and potential appetite-enhancing effects at specific dosages.